Combined finite-discrete element method modeling of rockslides. Issue 5 (4th July 2016) - Zhou, Wei; Yuan, Wei; Ma, Gang; Chang, Xiao-Lin
Abstract : Purpose: – The purpose of this paper is to propose a novel combined finite-discrete element method (FDEM), based on the cohesive zone model, for simulating rockslide problems at the laboratory scale. Design/methodology/approach: – The combined FDEM is realized using ABAQUS/Explicit. The rock mass is represented as a collection of elastic bulk elements glued by cohesive elements with zero thickness. To reproduce the tensile and shear micro-fractures in rock material, the Mohr-Coulomb model with tension cut-off is employed as the damage initiation criterion of cohesive elements. Three simulated laboratory tests are considered to verify the capability of combined FDEM in reproducing the mechanical behavior of rock masses. Three slope models with different joint inclinations are taken to illustrate the application of the combined FDEM to rockslide simulation. Findings: – The results show that the joint inclination is an important factor for inducing the progressive failure behavior. With a low joint inclination, the slope failure process is observed to be a collapse mode. As the joint inclination becomes higher, the failure mode changes to sliding and the steady time of rock blocks is shortened. Moreover, the runout distance and post-failure slope angle decrease as the joint inclination increases. Originality/value: – These studies indicate that the combined FDEM performed within ABAQUS can simulate slope stability problems for research purposes and is useful for studying the slope failure mechanism comprehensively.